Foreign Direct Investment in India and China: Some Lessons for India - Ramakrishna, H. (Indian Journal of Finance, 2011)
Foreign Direct Investment is an important form of foreign capital, which has become very crucial in the world economy since a decade and half. Liberalization, privatization and Globalization have led to internationalization of production, marketing and flow of capital through Multinational corporations. As FDI is backed with more advantages, there is a huge competition among developing countries, including India and China, to turn FDI to their nations. In the race of attracting FDI, China has outclassed USA also. Studies show that FDI companies contribute more for industrial output, and exports access to the market. In light of this, the present paper is a focus on the reasons for the low inflow of FDI to India on the one hand and the high inflow of FDI to China on the other.